Late pleistocene glaciations and paleoclimate of turkey - Sarikaya, M. Akif; Çi̇ner, Atilla (Bulletin of the Mineral Research and Exploration, 2015)
Glaciers respond quickly to climatic  changes and thus they are considered to be very accurate indicators of changes in atmospheric conditions. Similarly, the extent of past glaciers gives valuable insights into paleoclimatic changes. For this purpose, we reviewed the paleo-glaciated mountains where cosmogenic surface exposure dating was applied in Turkey. We also evaluated the paleoclimatic results obtained from these studies to provide a regional overview. Twenty-seven mountains in Turkey are high enough to support Quaternary valley glaciers or ice caps. The timing of glaciations was reported mainly by cosmogenic dating of moraines. We re-evaluated the dated sites and recalculated some of the published cosmogenic ages using the up-to-date production rates. The oldest geochronological records reported from the region belong to the glaciations before the globally defined Last Glacial Maximum (LGM). These glaciers developed probably during the beginning of the last glaciation (MIS 4; 71 ka ago) and stopped advancing at the end of the MIS 3 (at 29-35 ka ago). Later, glaciers expanded and reached to their most extensive locations during MIS 2 (after 29 ka ago). They reached maximum extents between 21.5 ka ago and 18.5 ka ago. This local-LGM was synchronous with the global-LGM. After the LGM, the glaciers started to retreat to less extensive positions and deposited their moraines ~16 ka ago during the Late Glacial. The Younger Dryas (~12 ka ago) advances were also reported from a limited number of mountains. Rare Early Holocene glaciations were dated to 8.5 ka in the interior regions. Late Holocene (1-4 ka ago) and Little Ice Age (between 1300-1850 AD) advances were also observed. We reconstructed the paleoclimate using glacier modeling together with paleoclimate proxy data from several regions. The results show that LGM climate was 8-11°C colder than today and moisture levels were 1.5 to 2 times in SW Turkey, somewhat similar to modern values in central parts and 30 % drier in the NE. The Late Glacial was colder by 4.5-6.4°C based on up to 50 % wetter conditions. The Early Holocene was 2.1-4.9°C colder and up to twice as wet as today, while the Late Holocene was 2.4-3°C colder and its precipitation amounts approached to similar conditions as today.
Keywords: Engineering; Mühendislik; Glacier; Late Pleistocene; Quaternary; Cosmogenic Surface Exposure Dating; Moraine; Paleoclimate